ANTIDEPRESSANT THERAPY IN PREGNANCY AND THE POSTPARTUM PERIOD: MODERN STRATEGIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Depression during pregnancy and the postpartum period is among the most common affective disorders in women of reproductive age, affecting up to 15%. It has a significant negative impact on both the mother’s mental health and the child’s development and well-being. Alongside psychotherapy, pharmacological methods—particularly antidepressants—play an important role in treatment. Despite concerns regarding the safety of antidepressants during pregnancy and breastfeeding, a growing body of research supports their effectiveness and relative safety when used appropriately.